Unlocking the therapeutic potential of N-heterocyclic derivatives as Pim kinase inhibitors - Rajarshi Nath; Arka Chakraborty; Lakshminarayan Das; Anhic Chakraborty; Sumel Asique; Sumit Maji; Sayan Bhattacharjee; Shah Alam Khan; Biplab Debnath; Md Jawaid Akhtar (Molecular Biology Reports, 2026)

Quorum sensing–mediated infochemical dialogue in the rhizosphere: Implications for plant stress resilience - Riti Pal; Rohini Verma; Sumit Kumar; Jangila Hazowary; Jayajeevitha SRM; Aayeisha Das; Aarti Bairwa; Debasis Mitra; Ali Chenari Bouket; Masoud Chamani; Udai B. Singh; R. Arutselvan; et al. (Rhizosphere, 2026)

Shaping SHAPE - A spectro-polarimeter onboard Chandrayaan-3 to observe Earth as an Exoplanet - Anuj Nandi; Swapnil Singh; Bhavesh Jaiswal; Anand Jain; Smrati Verma; Reenu Palawat; B.T. Ravishankar; Brajpal Singh; Priyanka Das; Supratik Bose; Supriya Verma; Waghmare Rahul Gautam; et al. (Advances in Space Research, 2026)

Productivity, carbon dynamics and soil fertility of eucalyptus based agroforestry system under different winter crops - Rakesh Panday; Dipty Kumar Das; Rajesh Kumar Meena; Soibam Lanabir Singh; Santosh Kumar Singh; Ritwik Sahoo; Prabhat Tiwari; Sumit Sow; Dibyajyoti Nath; Shivani Ranjan (Plant and Soil, 2026)

Engineered pectin-coated copper oxide nanocarriers for controlled fungicide release: a mechanistic exploration of fungal pectinase-mediated delivery and its role in advancing sustainable agriculture - Monika; Anubhav Naskar; Sumit Shekhar; Tirthankar Banerjee; Nabanita Mukherjee; Sumistha Das; Nitai Debnath (World Journal of Microbiology and Biotechnology, 2026)

Modeling climate-induced changes in hydrometeorological components and analyzing future extreme weather events using SPI in the Kosi River Basin, Uttarakhand - Biswajit Das; Sumit Sen; Sandipan Mukherjee (Theoretical and Applied Climatology, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Integrated morphometric and LULC change-based soil erosion risk prioritization in the Gaudi River sub-watersheds, Lesser Himalaya - Biswajit Das; Sumit Sen; Shivendra Narayan Singh (Natural Hazards, 2026)

Identification of Groundwater Potential Zones in North-Western Bankura, West Bengal, India, Using GIS Based MCDA Techniques TOPSIS and CoCoSo - Sumit Kar; Bikul Barman; Jayanta Das (Journal of the Indian Society of Remote Sensing, 2026)

Is there water sector transformation evident in policies? Experiences from Asia and Africa - Mijo Luke; Risper Ajwang’ Ondiek; Fides Izdori; Gitima Das; Sumit Vij (Environmental Science & Policy, 2026)

Anthropogenic infrastructure overrides natural drivers of sediment yield in a major monsoonal river basin - Sumit Das; Soumi Talukdar; Gianvito Scaringi (Science of The Total Environment, 2026)

Geochemistry and U–Pb Geochronology of Volcaniclastic Rocks From the NW Lesser Himalayan Sequence: Implications for Arc‐Related Tectonic Setting at Northern Proto‐Indian Continental Margin During the Neoproterozoic - Subhojit Saha; Kaushik Das; Shivani S. Choudhari; Abhishek Kumar Pandey; Shruti Ranjan Mishra; Sumit Kumar Ghosh; Alok Deep; Partha Pratim Chakraborty (Island Arc, 2026)
The protracted tectonic history concerning the northern edge of the pre‐Himalayan proto‐Indian plate margin during the Neoproterozoic time has been a long‐standing subject of debate, with various hypotheses enduring over several decades. Although a continental rift to passive margin setting has been proposed for the deposition of Neoproterozoic rocks of the Outer Lesser Himalayan Sequence (OLHS), the similarity in detrital zircon age peaks and Nd isotope values of OLHS rocks with those of the Higher Himalayan Crystalline Sequence (HHCS) led to the proposition of an arc‐related setting. So far, there is no such report of Neoproterozoic arc‐related magmatism from the Lesser Himalayan Sequence. In the present study, an interbedded volcaniclastic horizon has been identified from the basal stratigraphic level of the Nagthat Formation, OLHS. Geochemistry and U–Pb zircon geochronology are used to understand the provenance and tectonic setting of the Nagthat volcaniclastic rock. The angularity of the framework minerals, moderate degree of weathering (avg. Chemical Index of Alteration value 62), and immature nature (Index of Compositional Variability 1–1.1) suggest that a contemporaneous volcanic province was probably the main source. Whole rock geochemical analysis shows high Th/Sc (1.67–3.40, avg. 2.71), La/Sc (4.74–8.21, avg. 7.14), and low Cr/Th ratios (1.78–5.45, avg. 3.02). It supports that the volcaniclastic was supplied from an acid to intermediate source rocks, such as rhyolite and dacite/andesite. U–Pb detrital zircon analysis yielded a major age peak around 775 Ma. However, comparison of the U–Pb zircon age data with published datasets from the Lower (Chandpur Formation) and upper (Nagthat Formation) stratigraphic horizons suggests a timing of volcanism between 800 and 700 Ma. Geochronological and geochemical characteristics of the volcaniclastic rock suggest a signature transitional from passive to active continental margin setting, indicating that at least subduction was ongoing during the Tonian (800–700 Ma) at the northern proto‐Indian plate margin.

Sediment load decline and increased erosion linked to human activities in the Cauvery delta, India - Sumit Das; Harshada Jadhav; Aditi Roy; Gianvito Scaringi (CATENA, 2025)

Exploring the effects of ROS on PI3K/AKT/mTOR signalling in pediatric low-grade glioma and therapeutic strategies - Jayita Das; Nilanjan Adhikari; Ayan Pal; Tanaya Chongder; Samar Dule; Atanu Sarma; Sumit Dutta; Priyanka Gupta; Abhimannu Shome (Molecular Biology Reports, 2025)

Bi-functional carbonaceous hybrid nanocomposites with anticancer and antibacterial potential: synthesis, characterization, and cytotoxicity assessment - Juhi Saxena; Tarun Kumar Upadhyay; Anupam Jyoti; Unnati Joshi; Anand Joshi; Mahendra Singh Rathore; Sanketsinh Thakor; Jaivik Pathak; Sumit Das Lala; Payel Deb (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biofortified vermicompost: Exploring bacterial community dynamics and enzymatic pathways through bacteriome analysis for arsenic bioremediation in mine waste - Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Pritam Mukherjee; Souvik Das; Pradip Bhattacharyya (Environmental Pollution, 2025)

Study of Bay of Bengal cyclones for year 2023 using SCAT-3 and GFS datasets and numerical simulation of associated surges using SWAN + ADCIRC model - Ritama Das; Sumit Mondal; Anup Kumar Mandal; Neeru Jaiswal; Tushar Kanti Saha; Tarun Kumar De (Ocean Dynamics, 2025)

Local and broad-scale anthropogenic controls on sediment transport in the Western Ghats rivers, India - Sumit Das; Ali P. Yunus; Gianvito Scaringi; A.C. Narayana (Anthropocene, 2025)

Pan-cancer analysis of cancer-specific transcript isoforms reveals the regulatory impact of isoform switching on the alteration of the interplay between RBPs and miRNAs in cancers - Sukhen Das Mandal; Sumit Mukherjee (Journal of Biosciences, 2025)

Determination of beneficial effects of cuminaldehyde on hyperglycemia associated kidney malfunctions - Abhishek Kumar Das; Sumit Ghosh; Parames C. Sil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Silencing Nrf2 in cisplatin resistant non-small cell lung cancer cells augments sensitivity towards EGFR inhibitor - Chandrani Fouzder; Alpana Mukhuty; Dipanjan Chattopadhyay; Snehasis Das; Sumit Kumar Hira; Rakesh Kundu (Toxicology in Vitro, 2024)

In search of poly-3-hydroxybutyrate (PHB): A comprehensive review unveiling applications and progress in fostering a sustainable bio-circular economy - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Krishnendu Mondal; Ashish Kumar Singh; Sonia Tamang; Palash Hazra; Nagendra Thakur; Rajendra Bhanwaria; Sumit G Gandhi; Vinod Kumar (Food and Bioproducts Processing, 2024)

Unlocking Nature’s Stress Reliever: The Role of Melatonin in Enhancing the Resilience of Fruit Crops Against Abiotic Stress - Susmita Shil; Shubranil Das; Michi Tani; Jome Rime; Sumit Sow; Songthat William Haokip; Kh. Anush Sheikh; Mangalam S. Bhargava; Onam Pertin; Siddhartha Singh (Applied Fruit Science, 2024)

Tree species diversity and population dynamics and regeneration status in the tropical forest of Tripura: confluence of indo-burmese biodiversity hotspot - Amal Debnath; Saptadip Majumder; Bipul Das Chowdhury; Alekhya Sarkar; Sumit Kumar Das; Bimal Debnath (Vegetos, 2024)

Guggulsterone Selectively Modulates STAT-3, mTOR, and PPAR-Gamma Signaling in a Methylmercury-Exposed Experimental Neurotoxicity: Evidence from CSF, Blood Plasma, and Brain Samples - Sumit Kumar; Sidharth Mehan; Zuber Khan; Ghanshyam Das Gupta; Acharan S. Narula (Molecular Neurobiology, 2024)

The Emerging Role of Natural Products in Cancer Treatment - Sumit Ghosh; Sanjib Kumar Das; Krishnendu Sinha; Biswatosh Ghosh; Koushik Sen; Nabanita Ghosh; Parames C. Sil (Archives of Toxicology, 2024)

From waste management to circular economy: Leveraging thermophiles for sustainable growth and global resource optimization - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Sonia Tamang; Krishnendu Mondal; Nagendra Thakur; Sumit G. Gandhi; Vinod Kumar (Journal of Environmental Management, 2024)

Comments on “An effective geospatial-based flash flood susceptibility assessment with hydrogeomorphic responses on groundwater recharge” by Tariq et al.: Groundwater for Sustainable Development v. 23, no: 100998 - Sumit Das (Groundwater for Sustainable Development, 2024)

Microplastics contamination in two species of gobies and their estuarine habitat of Indian Sundarbans - Nilanjan Hari Chatterjee; Sumit Manna; Abhishek Ray; Sourav Das; Nabakumar Rana; Aritra Banerjee; Mitali Ray; Sajal Ray (Marine Pollution Bulletin, 2024)

Nonlocal effect on shear wave propagation in a fiber-reinforced poroelastic layered structure subjected to interfacial impulsive disturbance - Rachaita Dutta; Soumik Das; Neelima Bhengra; Sumit Kumar Vishwakarma; Sandip Kumar Das (Soil Dynamics and Earthquake Engineering, 2024)

Bibliometric analysis, physical properties, and experimental evaluation of additives-diesel ternary blends - Chandan Kumar; Mukesh Kumar; Umesh Kumar Das; Sumit Sharma (Environmental Science and Pollution Research, 2023)

Spatial diversity and habitat characteristics of seagrass meadows with management recommendations in the Andaman and Nicobar Islands, India - Swapnali Gole; Sumit Prajapati; Nehru Prabakaran; Himansu Das; Sivakumar Kuppusamy; Jeyaraj Antony Johnson (Frontiers in Marine Science, 2023)
The Andaman and Nicobar Islands, India, a geographically remote region, harbor a diverse island ecosystem. Limited exploration has hindered our understanding of marine floral biodiversity in this area. To address this gap, we investigated seagrass meadows in the Andaman and Nicobar Islands to understand their spatial distribution, species composition, and habitat characteristics. We assessed 66 seagrass meadows, including 32 newly discovered ones, filling data gaps in the region’s seagrass coldspots. Seagrasses were found across a wide range of depths, with the majority occurring in shallow subtidal waters (< 8 m). Large-sized species such as Thalassia hemprichii , Enhalus acoroides , Cymodocea rotundata , Cymodocea serrulata , and Syringodium isoetifolium dominated the littoral and shallow subtidal zones, while smaller species such as Halophila spp. and Halodule spp. exhibited broader depth distributions. H. beccarii and H. decipiens were strictly intertidal and subtidal species, respectively. Water depth significantly influenced seagrass occurrence (p < 0.0001), cover (β = -0.2759; SE = 0.02471; p < 0.0001), shoot densities (β = -0.3556; SE = 0.1231; p = 0.005), and biomass (β = -0.3526; SE = 0.1159; p = 0.003). Sand availability emerged as the second significant predictor of seagrass distribution, cover, and biomass (p values < 2e-16, < 2e-16, and 0.01, respectively). Habitat heterogeneity decreased with increasing water depth, and seagrass species exhibited strong preferences for specific substrata, resulting in spatial niche partitioning. Our study provides novel insights into the seagrass spatial diversity, habitat characteristics, and seagrass-environment relationship in the Andaman and Nicobar Islands. Further, it highlights the importance of water depth, habitat characteristics, and substratum heterogeneity in seagrass distribution and growth. Lastly, our findings imply that any change to the benthic profile of the meadows will influence the seagrass species distribution and growth. Understanding these factors is crucial for seagrass conservation and management in the region, aiding the development of targeted strategies to protect these valuable marine habitats and associated biodiversity.

The role of astrocytes in the glymphatic network: a narrative review - Nikita Das; Ravi Dhamija; Sumit Sarkar (Metabolic Brain Disease, 2023)

Identifying the tectonically induced mineralisation zone in the central part of Dharwar-Shimoga greenstone belt, Western Dharwar Craton: an integrated analysis of gravity and magnetic data - Niharika Das; Sumit Kumar Bhattacharya; Satya Narayan; D. Livingston (Acta Geophysica, 2023)

The Flower Colour Influences Spontaneous Nectaring in Butterflies: a Case Study with Twenty Subtropical Butterflies - Sumit Kumar Sinha; Avishek Dolai; Arjan Basu Roy; Sourav Manna; Amlan Das (Neotropical Entomology, 2023)

Link between Lesser Himalayan Neoproterozoic Krol succession and the Adelaide rift complex of Australia ‒ evidence from the mudstone deposits of Krol succession, Himachal Pradesh, India - Sumit Dey; Prabir Dasgupta; Kaushik Das; Abdul Matin (Marine and Petroleum Geology, 2023)

A non-destructive approach to develop tree-level allometric equations for estimating aboveground biomass in the forests of Tripura, Northeast India - Abhilash Dutta Roy; Sumit Kumar Das; Bimal Debnath (Tropical Ecology, 2023)

Interrelation between factors controlling sediment yield in the largest catchment of Peninsular India - Sumit Das; Satish J. Sangode; Avinash M. Kandekar; Dhananjay C. Meshram; Paolo Tarolli (Journal of Hydrology, 2023)

OGF nanocomposite foam for enhanced recyclability and oil-recovery - Dharmveer Yadav; Rahul Kumar Das; Sumit Saxena; Shobha Shukla (Journal of Cleaner Production, 2023)

A mis-splicing early flowering 3 (elf3) allele of lentil is associated with yield enhancement under terminal heat stress - Anirban Roy; M. Hemakumar Reddy; Moutushi Sarkar; Diana Sagolsem; Sumit K. Murmu; Camellia Das; Debarati Roy; Shamba Ganguly; Rajib Nath; Prabir K. Bhattacharyya; Asutosh Sarker; Somnath Bhattacharyya (Journal of Applied Genetics, 2023)

Scale-dependency, rainfall, and lithologic controls on the hypsometry of the Western Ghats, India - Sreejita Banerjee; Sumit Das; Avinash M Kandekar; Gianvito Scaringi; Satish J Sangode (Journal of Earth System Science, 2023)

4D nanoprinted sensor for facile organo-arsenic detection: A two-photon lithography-based approach - Sweta Rani; Rahul Kumar Das; Arun Jaiswal; Gaurav Pratap Singh; Ajinkya Palwe; Sumit Saxena; Shobha Shukla (Chemical Engineering Journal, 2023)

Melatonin induces apoptosis and cell cycle arrest in cervical cancer cells via inhibition of NF-κB pathway - Tarun Minocha; Megha Das; Vipin Rai; Sumit Singh Verma; Nikee Awasthee; Subash Chandra Gupta; Chandana Haldar; Sanjeev Kumar Yadav (Inflammopharmacology, 2022)

Evaluation of Styrylbenzene analog- FSB and its affinity to bind parenchymal plaques and tangles in patients of Alzheimer’s disease - Sharay E. Setti; Nikita Das; James Raymick; Joseph Hanig; Sumit Sarkar (Metabolic Brain Disease, 2022)

Risk estimation of soil slope stability problems - Guru Das; Avijit Burman; Abidhan Bardhan; Sumit Kumar; Shiva Shankar Choudhary; Pijush Samui (Arabian Journal of Geosciences, 2022)

River flooding in a changing climate: rainfall-discharge trends, controlling factors, and susceptibility mapping for the Mahi catchment, Western India - Sumit Das; Gianvito Scaringi (Natural Hazards, 2021)

Role of metals in Alzheimer’s disease - Nikita Das; James Raymick; Sumit Sarkar (Metabolic Brain Disease, 2021)

Evaluation of the benefits of assimilation of Meteosat-8 observations in an NWP system over the Indian Ocean region - M. T. Bushair; S. Indira Rani; Buddhi Prakash Jangid; Priti Sharma; Sumit Kumar; John. P. George; M. Das Gupta (Meteorology and Atmospheric Physics, 2021)

Variation in P-acquisition ability and acid phosphatase activity at the early vegetative stage of lentil and their validation on P-deficiency field - Shamba Ganguly; Anirban Roy; Sumit K. Murmu; Diana Sagolsem; Moutushi Sarkar; Shubhrajyoti Sen; Dibakar Das; Camellia Das; Prabir Chakraborty; Prabir K. Bhattacharyya; Rajib Nath; Kuldeep Tripathi; et al. (Acta Physiologiae Plantarum, 2021)

Investigation of changes in seasonal streamflow and sediment load in the Subarnarekha-Burhabalang basins using Mann-Kendall and Pettitt tests - Sumit Das; Sreejita Banerjee (Arabian Journal of Geosciences, 2021)

Diversity, community characteristics and regeneration status of tree species in Rowa Wildlife Sanctuary: an Indo-Burmese Hotspot—Tripura, North East India - Bimal Debnath; Sumit Kumar Das; Amal Debnath (Vegetos, 2021)

Analysis of genetic diversity of Colletotrichum population causing anthracnose in fruit crops using ISSR markers - Amrita Das; Buddhadeb Roy; Sumit Jangra; Amita Chowdhury; Deeba Kamil; T. Prameela Devi (Indian Phytopathology, 2021)

Hydro-chemical characterization and geospatial analysis of groundwater for drinking and agricultural usage in Nashik district in Maharashtra, India - Rajendra B. Zolekar; Rahul S. Todmal; Vijay S. Bhagat; Santosh A. Bhailume; Mahendra S. Korade; Sumit Das (Environment, Development and Sustainability, 2021)

Significance of geographical factors to the COVID-19 outbreak in India - Amitesh Gupta; Sreejita Banerjee; Sumit Das (Modeling Earth Systems and Environment, 2020)

Epoxyazadiradione exhibit activities in head and neck squamous cell carcinoma by targeting multiple pathways - Vipin Rai; Sushil Kumar Aggarwal; Sumit Singh Verma; Nikee Awasthee; Anupam Dhasmana; Sadhna Aggarwal; Satya N. Das; Mangalam S. Nair; Sanjay Yadav; Subash C. Gupta (Apoptosis, 2020)

Four decades of water and sediment discharge records in Subarnarekha and Burhabalang basins: an approach towards trend analysis and abrupt change detection - Sumit Das (Sustainable Water Resources Management, 2019)

Exposure to watermelon bud necrosis virus and groundnut bud necrosis virus alters the life history traits of their vector, Thrips palmi (Thysanoptera: Thripidae) - Amalendu Ghosh; Y. B. Basavaraj; Sumit Jangra; Amrita Das (Archives of Virology, 2019)

Effect of ions and inhibitors on the catalytic activity and structural stability of S. aureus enolase - Vijay Hemmadi; Avijit Das; Om Prakash Chouhan; Sumit Biswas; Malabika Biswas (Journal of Biosciences, 2019)

Geomorphic characteristics of a bedrock river inferred from drainage quantification, longitudinal profile, knickzone identification and concavity analysis: a DEM-based study - Sumit Das (Arabian Journal of Geosciences, 2018)

Geographic information system and AHP-based flood hazard zonation of Vaitarna basin, Maharashtra, India - Sumit Das (Arabian Journal of Geosciences, 2018)

Climate change perceptions and response strategies of forest fringe communities in Indian Eastern Himalaya - Tanusri Dey; Nazir A. Pala; Gopal Shukla; Prabhat K. Pal; Ganesh Das; Sumit Chakarvarty (Environment, Development and Sustainability, 2018)

Morphological determinants of dendritic arborization neurons in Drosophila larva - Sumit Nanda; Ravi Das; Shatabdi Bhattacharjee; Daniel N. Cox; Giorgio A. Ascoli (Brain Structure and Function, 2018)

Extraction of lineaments from different azimuth angles using geospatial techniques: a case study of Pravara basin, Maharashtra, India - Sumit Das; Sudhakar D. Pardeshi; Pallavi P. Kulkarni; Arjun Doke (Arabian Journal of Geosciences, 2018)

Comparative analysis of lineaments extracted from Cartosat, SRTM and ASTER DEM: a study based on four watersheds in Konkan region, India - Sumit Das; Sudhakar D. Pardeshi (Spatial Information Research, 2018)

Identification of morphogenetic regions and respective geomorphic processes: a GIS approach - Arjun Doke; Sudhakar D. Pardeshi; Suchitra S. Pardeshi; Sumit Das (Arabian Journal of Geosciences, 2018)

Exploring groundwater potential zones using MIF technique in semi-arid region: a case study of Hingoli district, Maharashtra - Sumit Das; Amitesh Gupta; Sasanka Ghosh (Spatial Information Research, 2017)

Etoposide and doxorubicin enhance the sensitivity of triple negative breast cancers through modulation of TRAIL-DR5 axis - Sarita Das; Neha Tripathi; Sumit Siddharth; Anmada Nayak; Deepika Nayak; Chinmayee Sethy; Prasad V. Bharatam; Chanakya Nath Kundu (Apoptosis, 2017)

Verification of dust forecast over the Indian region with satellite and ground based observations - Prasenjit Das; John P. George; Sumit Kumar (International Journal of Remote Sensing, 2016)

SURVIVIN as a marker for quiescent-breast cancer stem cells—An intermediate, adherent, pre-requisite phase of breast cancer metastasis - Sumit Siddharth; Sarita Das; Anmada Nayak; Chanakya Nath Kundu (Clinical & Experimental Metastasis, 2016)

An efficient in vitro regeneration system of fieldpea (Pisum sativum L.) via. shoot organogenesis - Alok Das; Sumit Kumar; P. Nandeesha; Indu Singh Yadav; Jyoti Saini; S. K. Chaturvedi; Subhojit Datta (Journal of Plant Biochemistry and Biotechnology, 2014)

Interrelationship Between Procalcitonin and Organ Failure in Sepsis - Dimple Anand; Sabari Das; Sumit Ray; Seema Bhargava; Lalit Mohan Srivastava (Indian Journal of Clinical Biochemistry, 2014)